2015
DOI: 10.1371/journal.pone.0127287
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Focused PCR Array Profiling of Enriched Populations of Laser Capture Microdissected Hippocampal Cells after Traumatic Brain Injury

Abstract: Cognitive deficits in survivors of traumatic brain injury (TBI) are associated with irreversible neurodegeneration in brain regions such as the hippocampus. Comparative gene expression analysis of dying and surviving neurons could provide insight into potential therapeutic targets. We used two pathway-specific PCR arrays (RT2 Profiler Apoptosis and Neurotrophins & Receptors PCR arrays) to identify and validate TBI-induced gene expression in dying (Fluoro-Jade-positive) or surviving (Fluoro-Jade- negative) pyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 74 publications
1
22
0
Order By: Relevance
“…Three 10 μm-thick cryosections were prepared and air dried. PixCell Iie system (Arcturus Engineering, Mountain View CA) were employed to perform LCM according to the manufactures protocol [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Three 10 μm-thick cryosections were prepared and air dried. PixCell Iie system (Arcturus Engineering, Mountain View CA) were employed to perform LCM according to the manufactures protocol [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Multiple recent studies have shown that axonal degeneration is connected to increased axolemmal permeability, disruption of axoplasmic transport, mitochondrial swelling, and cytoskeletal (microtubule and neurofilament structures) compaction damage 6 , 7 . Moreover, neuronal cell apoptosis is another important mechanism in the loss of nerve function following DAI and is induced by endoplasmic reticulum (ER) stress, inflammatory mediators, oxygen free radicals, excitatory neurotransmitters, or Ca 2+ overload 8 , 9 . Therefore, studies on the effects of drugs on axonal injury or neuronal cell apoptosis after DAI can provide insights into potential treatments for DAI in a clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…These regions include those identifiable with conventional LCM-compatible stains, such as cresyl violet or hematoxylin and eosin. The speed of the laser-capture process and ability to perform LCM on thicker 30 µm sections on PEN membrane slides allows to not only obtain sufficient quantities of cell samples, but also to isolate RNA from LCM samples of a suitable quality for all types of downstream genomic analysis; these analyses include microarrays 16 , PCR arrays 17 , and quantitative real-time PCR 18 .…”
Section: Discussionmentioning
confidence: 99%